Incidence of celiac disease autoimmunity and associations with maternal tuberculosis and pediatric Helicobacter pylori infections in 4-year-old Ethiopian children followed up in an HLA genotyped birth cohort - Gudeta, Adugna Negussie; Andrén Aronsson, Carin; Binagdie, Bayissa Bekele; Girma, Alemayehu; Agardh, Daniel (Frontiers in Pediatrics, 2022)
Background: The prevalence of celiac disease in the general population is mainly unknown in most of Sub-Saharan African countries. The aim of this study was to determine the incidence of celiac disease autoimmunity (CDA) and its associations with latent Mycobacterium tuberculosis (LMTB) and Helicobacter pylori (HP) infections in Ethiopian children by age 4 years in HLA genotyped cohort study. Methods: Of 1,389 recruited children between 2018 and 2022, 1046 (75.3%) children had been screened at least twice for celiac disease between the ages of two and four years using a tissue transglutaminase autoantibody (tTGA) ELISA kit. Tissue TGA-positive children were retested using radio-binding assays (RBA). Celiac disease autoimmunity (CDA) was defined as persistent-confirmed tTGA positivity in two consecutive samples. Associations of CDA with LMTB and HP were tested in a subpopulation of 752 children born to mothers who were previously tested for LMTB with IFN-γ and anti-HP antibodies in samples collected at mean age of 49.3 ±5.3 months, respectively. Results: Screening detected 38 out of 1046 (3.6%) IgA-tTGA positive children. Ten (1.0%) were confirmed positive, with six (0.6%) children diagnosed with CDA. Incidence of CDA by age 4 years was 1.2 per 1000 person-years. LMTB was found in 4/6 (66.7%) mothers with CDA children compared with 340/734 (46.3%) mothers of children without CDA (p=0.424), while HP was found in 3/6 (50.0%) CDA children compared with 315/746 (42.2%) children without CDA (p=0.702). Conclusion: Incidence of CDA in Ethiopian children is lower than the pooled global incidence. Neither LMTB nor HP infections are associated with CD in Ethiopian children.